2021
DOI: 10.1177/0734242x211008526
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance analysis of support vector regression and artificial neural network for prediction of municipal solid waste generation

Abstract: The evolution of machine learning (ML) algorithms provides researchers and engineers with state-of-the-art tools to dynamically model complex relationships. The design and operation of municipal solid waste (MSW) management systems require accurate estimation of generation rates. In this study, we applied rapid, non-linear and non-parametric data driven ML algorithms independently, multi-layer perceptron artificial neural network (MLP-ANN) and support vector regression (SVR) models to predict annual MSW genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The burial depth of grade II-III surrounding rock tunnel is 20-220 m, the thickness of shotcrete is 2-6 cm, the length of bolt is 1.5-2 m, and the dilatation angle is 10 °-18 °. The horizontal side pressure coefficient is taken as 0.5∼1.5, the bolt spacing is taken as 1 m, the bolt diameter is taken as 18∼22 mm, the surrounding rocks of grades II-III are divided into 11 levels, and the surrounding rocks of grades IV-V are divided into 26 levels; according to the uniform experimental design method, 37 numerical test schemes are combined [15,16].…”
Section: Acquisition Of Training Samples: Numericalmentioning
confidence: 99%
“…The burial depth of grade II-III surrounding rock tunnel is 20-220 m, the thickness of shotcrete is 2-6 cm, the length of bolt is 1.5-2 m, and the dilatation angle is 10 °-18 °. The horizontal side pressure coefficient is taken as 0.5∼1.5, the bolt spacing is taken as 1 m, the bolt diameter is taken as 18∼22 mm, the surrounding rocks of grades II-III are divided into 11 levels, and the surrounding rocks of grades IV-V are divided into 26 levels; according to the uniform experimental design method, 37 numerical test schemes are combined [15,16].…”
Section: Acquisition Of Training Samples: Numericalmentioning
confidence: 99%
“… Kontokosta et al (2018) , on the other hand, concluded that climatic variables were vital features in their ANN waste prediction models at New York. Recently, Jassim et al (2021) used various environmental related parameters such as annual tourist numbers, annual electricity consumption, and total annual CO2 emissions to model MSW generation rates in Bahrain.…”
Section: Introductionmentioning
confidence: 99%
“…When the model performs inference, it will take up more memory. However, the amount of calculation puts a load on the computing resources of the mobile phone processor, and a large amount of calculation will keep the mobile phone in working state, which will have a certain impact on the battery life of the mobile phone [11,12]. Therefore, focusing on the amount of parameters and calculation can directly affect the size of the model, thereby indirectly affecting the memory, battery life, performance and other issues of the mobile phone [13,14].…”
Section: Analysis Of Research Significancementioning
confidence: 99%